Sistem Pendukung Keputusan Rekomendasi Pemberian Remisi Pada Narapidana Menggunakan Metode Topsis (Studi Kasus Pada Lembaga Pemasyarakatan Klas II-A Palu) - Dodu, A.Y. Erwin; Anshori, Yusuf; Limbong, Dennis Tandi (ScientiCO : Computer Science and Informatics Journal, 2018)
Remission is a reduction of criminal punishment given to prisoners who have been regulated in the laws of the Republic of Indonesia. The process of giving scores to inmates in Class IIA Palu Correctional Institution with certain criteria aims to facilitate the employees of Palu Class IIA to get recommendation of remission of prisoners. The decision support system in this research uses Technique for Order Preference method by Similiarity to Ideal Solution ( TOPSIS) which is one of the multicriteria decision-making methods, where the basic idea of this method is that the chosen alternative has the closest distance to the ideal solution and the furthest from the ideal negative solution. In determining the inmates who receive remission recommendation in Correctional Institution Class IIA Palu there are 6 criteria which become the basis of decision making such as health condition, special skill and leadership skill, social life, never breaking order and not being a recidivist. The final result in this study is the result of calculation of proximity relative to the ideal solution that is sorted from the highest value to the lowest value so that employees of Correctional Institution Class IIA can easily take a decision on remission recommendations by looking at the results of the sorting